2001
DOI: 10.1590/s1516-89132001000200001
|View full text |Cite
|
Sign up to set email alerts
|

Microflora dynamics in earthworms casts in an artificial soil (biosynthesol) containing lactic acid oligomers

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Result of this study showed the presence of several bacterial and fungal species in the different earthworm cast examined. This agrees with the findings of several authors who had reported the occurrence of several species of bacteria and fungi in earthworm casts (Alauzet, et al, 2001;Prakash, et al, 2008;Jayakumar, et al, 2009). Microorganisms generally flourish in earthworm casts (Domsch and Banse 1972).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Result of this study showed the presence of several bacterial and fungal species in the different earthworm cast examined. This agrees with the findings of several authors who had reported the occurrence of several species of bacteria and fungi in earthworm casts (Alauzet, et al, 2001;Prakash, et al, 2008;Jayakumar, et al, 2009). Microorganisms generally flourish in earthworm casts (Domsch and Banse 1972).…”
Section: Discussionsupporting
confidence: 93%
“…The presence of the fungi Aspergillus, Penicillium and Fusarium in the earthworms casts is not surprising as the genera Aspergillus and Penicillium are frequently found in soils (Torres et al, 1999;Alauzet, et al, 2001). Tiunov and Scheu (2000) reported that the biomass of fungi is higher in Lumbricus terrestris casts than in the surrounding soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Alauzet et al [29], PLA ester hydrolysis in abiotic aqueous media depends on autocatalysis via chain end carboxylic groups and diffusion reaction phenomena involving water and oligomer molecules formed by degradation by means of its solubility in aqueous media. When submitted to heat and water, high molecular weight PLLA degrade to oligomer (PLA of low molecular weight), dimer and monomer of lactic acid.…”
Section: Biodegradation In Simulated Compost Soilmentioning
confidence: 99%
“…However, fungal growth decreased towards end of the experiment. It has been reported that earthworms feed on fungi for their protein/nitrogen requirement (Cooke, 1983;Moody et al, 1995;Ranganathan and Parthasarathi, 2000;Edwards, 2004), which was probably the reason for the less diversity of fungal counts at the end of the vermicomposting process (Alauzet et al, 2001;Nagavallemma et al, 2006). Bacterial count decreased gradually from the 0 to 15 days and further to 60 days of processing.…”
Section: Temporal Variation Of Microorganismsmentioning
confidence: 99%